Статическая роль мышц грудной конечности некоторых млекопитающих - Манзий, С.Ф.; Мороз, В.Ф. (Вестник зоологии, 1975)
The activity of thoracic limb muscles was studied by means of electromyography in representatives of digitigrades and unguligrades in statics. It is established that statics is an active process in all animals but the value of the muscle activity is not the same and depends on the value of static angles of the limb joints: the more acute the angles, the higher the muscle activity.